Evaluation of sample pooling for gene sequencing of SARS-CoV-2: a simulation study - Heng Chen; Yue Cheng; Xun He; Yuzhen Zhou; Wenjun Xie; Danyun Shen; Zhiqun He; Ruidan Li; Weixuan Liu; Liang Wang; Xuejun Zhang (Journal of Infection in Developing Countries)
Introduction: Coronavirus disease 2019 (COVID-19) continues to pose a significant public health threat, requiring epidemiological and genomic surveillance. Next generation sequencing (NGS) is commonly utilized for monitoring viral evolution at a high cost. This study evaluated pooled sequencing as a cost-effective tool for monitoring virus variants.